Nyāya Sữtra jako zmiana epistemiczna - Sikora, Sławomir (Investigationes Linguisticae, 2012)
The work concerns the problem of comparative research methodology and methods of argument in the philosophical systems of culturally diverse areas. The analysis and comparison is part of the Indian system of philosophical and epistemological – religious Nyāya Sữtra. The Nyāya Sữtra is interpreted in semiotic theory Ch. S. Peirce. On the basis of certain assumptions artificial intelligence and the theory of belief change, constructed for the semiotic model. As a result of the study shows that, in the epistemological Nyāya Sữtra is a system of acquiring knowledge. This system is characterized by abductive argumentation, and is aimed at the changing attitudes epistemic.